2003
DOI: 10.1076/apab.111.1.36.15143
|View full text |Cite
|
Sign up to set email alerts
|

ERK Inhibition Attenuates 5-HT-Induced Contractions in Fetal and Adult Ovine Carotid Arteries

Abstract: Growth and differentiation-related pathways are much more active in immature than in mature, fully differentiated smooth muscle. Because mitogen-activated protein kinases (MAPK) are intimately involved with growth and differentiation, and the extracellular signal-regulated kinase (ERK) subfamily of MAPKs are involved in some contractile responses, the present studies examined the hypothesis that ERKs play an important and age-dependent role in smooth muscle contraction. The MAPK inhibitors PD098059 and UO126 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Our results are well in line with the findings that specific ERK1/2 pathway inhibitors PD098059 and UO126 inhibited contractile responses to 5-HT in carotid arteries of sheep and that 5-HT can activate the ERK1/2 pathway in arterial smooth muscle through activation of 5-HT 2A receptors (Xu et al 2002). It is further supported by the fact that 5-HT 2A mediated-contraction is partly dependent on ERK1/2 activation (Banes et al 1999;Pearce et al 2003). Interestingly, one study has revealed the inability of 5-HT to activate JNK and p38 kinase pathways in rat aortic vascular smooth muscle cells (Banes et al 2001).…”
Section: Discussionmentioning
confidence: 63%
“…Our results are well in line with the findings that specific ERK1/2 pathway inhibitors PD098059 and UO126 inhibited contractile responses to 5-HT in carotid arteries of sheep and that 5-HT can activate the ERK1/2 pathway in arterial smooth muscle through activation of 5-HT 2A receptors (Xu et al 2002). It is further supported by the fact that 5-HT 2A mediated-contraction is partly dependent on ERK1/2 activation (Banes et al 1999;Pearce et al 2003). Interestingly, one study has revealed the inability of 5-HT to activate JNK and p38 kinase pathways in rat aortic vascular smooth muscle cells (Banes et al 2001).…”
Section: Discussionmentioning
confidence: 63%
“…These proteins mediate the Ca 2+ -independent activation of the contractile machinery and, therefore, represent markers of the Ca 2+ -independent contractile phenotype. While a similar reduction in the ERK1/2 protein level has been reported in developing ovine carotid arteries (Pearce et al 2003), such changes have not yet been described, to the best of our knowledge, for p38 MAPK and RhoK. Notably, inhibition of RhoK activity results in a more prominent depression of contraction in developing saphenous arteries than in arteries from adults rats (Mochalov et al 2008).…”
Section: Regulatory Protein Expression Is Altered Along With Ca 2+ Sementioning
confidence: 77%
“…Controversial reports are available regarding 5-HT-mediated signal transduction via MAPKs in vasculature. For instance, 5-HT-mediated contraction is mediated by ERK1/2 activation [10,50,59] and p38 MAPK [20,34,54]. On the other hand, Banes et al [3] found that 5-HT could not activate p38 MAPK and JNK in rat aortic vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…2, Table 1). [10,20,50,59]. Pretreatment of carotid arteries with each inhibitor as an MEK/ERK pathway inhibitor PD98059 (10 μmol L −1 ) (Fig.…”
Section: -Ht-and Norepinephrine-induced Contractionmentioning
confidence: 99%
See 1 more Smart Citation